2000
DOI: 10.1046/j.1365-2133.2000.03887.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping of epidermal dendritic cells allows the differentiation between extrinsic and intrinsic forms of atopic dermatitis

Abstract: While IAD is clinically similar to EAD, the inflammatory microenvironment in this condition seems different from classical EAD and can be distinguished by phenotyping of epidermal DCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2001
2001
2004
2004

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 19 publications
1
45
1
Order By: Relevance
“…However, this upregulation of FcεRI surface expression cannot be observed when monocytes from patients with intrinsic AD are analyzed [21]. Lesional skin from intrinsic AD, although clinically similar to extrinsic AD, can be distinguished by a much lower FcεRI surface expression on epidermal DC [22].…”
Section: Fcεri Expression On Antigen-presenting Cells Is Associated Wmentioning
confidence: 96%
“…However, this upregulation of FcεRI surface expression cannot be observed when monocytes from patients with intrinsic AD are analyzed [21]. Lesional skin from intrinsic AD, although clinically similar to extrinsic AD, can be distinguished by a much lower FcεRI surface expression on epidermal DC [22].…”
Section: Fcεri Expression On Antigen-presenting Cells Is Associated Wmentioning
confidence: 96%
“…This subgroup of AD, with the patients having normal IgE levels, has been labelled the intrinsic form of AD (IAD) [4]. In addition, epidermal dendritic cells of IAD patients have decreased levels of the high-affinity IgE receptor as compared with extrinsic AD (EAD) patients [5]. We have previously reported that both EAD patients (those having IgE sensitization) as well as IAD patients demonstrate predominantly T cells in the cellular infiltrate in eczematous skin lesions [6], suggesting a potential role of these cells in the pathogenesis of AD independent of IgE antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, patients may initially be considered having a nonallergic AEDS, but during the allergologic workup they may need to be reclassified as allergic AECS and vice versa. While nonallergic is clinically similar to allergic AEDS, the inflammatory microenvironment in these conditions seems to be different from classical allergic AEDS and can be clearly distinguished by phenotyping of epidermal dendritic cells (70).…”
Section: Nonallergic Aedsmentioning
confidence: 99%